Renormalization methods : a guide for beginners - McComb, W. D. (Oxford University Press, 2007)
There is currently widespread interest in applications of renormalization methods to various topics ranging from fluid turbulence to fluctuations in the stock market. This book is unique in demystifying this material for non-specialists. - ;This book is unique in occupying a gap between standard undergraduate texts and more advanced texts on quantum field theory. It covers a range of renormalization methods with a clear physical interpretation (and motivation), including mean-field theories and high-temperature and low-density expansions. It then proceeds by easy steps to the famous epsilon-ex.